Chameleon inspired layer-by-layer assembly of thermochromic microcapsules to achieve controllable multiple-color change. (16th March 2020) - Cao, Liangliang; Fang, Liang; Li, Xue; Chen, Shunping; Lu, Chunhua; Xu, Zhongzi
Abstract: Chameleons are attractive animals, which can change their colors because of unique layered skin structures. Inspired by this natural design, we explored a layer-by-layer assembly technique to create thermochromic films that can attain reversible and multiple-colors change. Briefly, inorganic pigments and two kinds of thermochromic microcapsules having different responsive temperatures were assembled sequentially onto a piece of filter paper using extraction filtration before epoxy resin was used to seal the whole structure. Different functions including colorful patterns and luminescent letters can be integrated into the system using this versatile approach. More importantly, arrays of thermochromic films were used with a detector and a heating-control circuit to trigger complicated color change by varying detected colors. We believe that this cost-efficient and convenient approach can be used in multiple applications such as camouflage, anti-counterfeiting, smart constructions and buildings, etc.